Nogeens: Sending en Evangelisasie. Onderlinge verhouding, draagwydte en strukturering - Kritzinger, J. J. (Verbum et ecclesia, 1994)
Yet again: mission and evangelism. Mutual relationship, range and structuring In the past the distinction between "mission" and "evangelism" was usually seen in an outreach to different categories of people. Mission, it was said, has to do with "not-yet-Christians", whereas evangelism tries to win hack "no-more-Christians". The theological reason for the distinction was the presence or absence of (previous) covenant relations. Nowadays it is preferred to differentiate rather on the basis of an understanding of the essence of the two activities. Mission is understood as the broader activity of the church’s involvement with the world, while evangelism is seen as the explicitly evangelising dimension of mission.